Static and Dynamic Mechanical Properties of Long-Span Cable-Stayed Bridges Using CFRP Cables - Mei Kuihua; Sun Shengjiang; Jin Guoqing; Sun Yamin (Advances in Civil Engineering)
The elastic modulus and deadweight of carbon fiber-reinforced polymer (CFRP) cables are different from those of steel cables. Thus, the static and dynamic behaviors of cable-stayed bridges using CFRP cables are different from those of cable-stayed bridges using steel cables. The static and dynamic performances of the two kinds of bridges with a span of 1000 m were studied using the numerical method. The effects of geometric nonlinear factors on static performance of the two kinds of cable-stayed bridges were analyzed. The live load effects and temperature effects of the two cable-stayed bridges were also analyzed. The influences of design parameters, including different structural systems, the numbers of auxiliary piers, and the space arrangement types of cable, on the dynamic performance of the cable-stayed bridge using CFRP cables were also studied. Results demonstrate that sag effect of the CFRP cable is much smaller than that of steel cable. The temperature effects of CFRP cable-stayed bridge are less than those of steel cable-stayed bridge. The vertical bending natural vibration frequency of the CFRP cable-stayed bridge is generally lower than that of steel cable-stayed bridge, whereas the torsional natural vibration frequency of the former is higher than that of the latter.